The Impact of the U.S.-China Tariff War on International Trade - Iglesia, Maria Joy Casano; Khan, Zafar; Nuzula, Ifta Firdausa (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to analyze the trade flows (imports, exports, and re-exports) of the world's two largest economies, namely China and the United States, during the period 2020 to 2023. Trading data is measured in USD units and includes three main types of trading flows. The visualization results show that China consistently maintains a trade surplus, with the value of exports always exceeding imports every year. In contrast, the United States shows a trade deficit trend, with the value of imports significantly higher than exports and re-exports. In addition, the role of re-exports in the trade structure of the United States showed a significant contribution, although not enough to balance the deficit. These findings provide important insights for global economic analysis and international trade policy, especially in the context of the dynamics of economic relations between the two superpowers.